School-based intervention on behavioral intention of adolescents regarding healthy diet in India - Jha, Sweety Suman; Dobe, Madhumita; Taklikar, Chandrashekhar; Lahiri, Arista (Frontiers in Public Health, 2023)
Introduction: Adolescence is a distinctive period of life when intense physical, psychological, and cognitive development occurs. A healthy diet helps prevent various forms of malnutrition and non-communicable diseases (NCDs) like diabetes, heart disease, stroke, and cancer. The current study aimed to assess the change in behavioral intentions (measured based on the TPB) towards healthy dietary practices through health promotion intervention among adolescents studying in selected schools in an urban area of West Bengal, India Methods: The current study was a non-randomized controlled interventional study conducted among adolescents in either seventh, eighth, ninth, or tenth grades and aged between 12 to 16 years. Two-step cluster analysis with maximum likelihood estimation identified the intenders of a healthy diet. The intervention effect was measured using Relative Risk (RR) for being in the higher intention cluster through Generalized Linear Model (GLM) with a log-linear link under Poisson distribution assumptions and robust standard errors. A P-value of 0.05 or lesser was considered statistically significant. Results: There was no statistically significant difference in the mean score of ‘Attitude’ in both groups. The mean score of ‘Subjective Norm’ among the intervention group increased after intervention, and the difference was statistically significant. The mean score of ‘Perceived behavioral control’ in the intervention group increased after the intervention, but the difference was statistically not significant. The intervention group’s post-intervention proportion of intenders increased, and the difference was statistically significant. The relative risk of becoming an intender for healthy diet consumption in the Intervention group compared to the Control group was 2.07 (1.44 – 2.97). Conclusions: The intervention package effectively brought about a positive change in behavioral intention toward healthy dietary practices among adolescents. Model-based and construct-oriented intervention packages can be adopted in school-setting to promote behavioral intention toward a healthy diet.